Potato yellow mosaic virus: A synonym of Tomato yellow mosaic virus - Morales, Francisco José; Lastra, R; Uzcategui, RC; Calvert, Lee A. (Springer, 2001)
Tomato yellow mosaic was first described in 1963, as a disease caused by a geminivirus transmitted by the whitefly Bemisia tabaci in Venezuela. In 1981 and 1985, Tomato yellow mosaic virus (ToYMV) was reported to occasionally infect potato plants growing in the proximity of tomato plantings affected by this virus. Despite these previous reports, a virus isolated from yellow mosaic-affected potato plants in Venezuela, was described in 1986 as a new geminivirus called potato yellow mosaic virus (PYMV). In recent years, different geminiviruses related to PYMV have been described from tomato fields in Venezuela and other countries in the Caribbean Basin, including Panama. Comparative nucleotide and amino acid sequence analyses of a 1698?bp fragment amplified from the common region and part of the AV1 and AC1 ORFs of ToYMV from Venezuela, yielded 95.7% sequence identity with the corresponding regions of PYMV. Nucleotide and amino acid sequence identities between ToYMV and PYMV, were 96.3% and 95.1% for AC1, and 95.7% and 100% for AV1, respectively. The identity of the nucleotide sequence for the common region of ToYMV and PYMV was 96.5%. Comparative sequence analyses conducted with ToYMV and other tomato begomoviruses present in the Caribbean region, showed only distant relationships. It is concluded here that PYMV is a synonym of ToYMV.